Valoración de la carga postural y riesgo musculoesquelético mediante el método reba en trabajadores de cultivo y cosecha de cacao injerto en fincas del cantón Mocache - Zambrano Bustillos, María Isabel (2022)
Musculoskeletal disorders are an occupational health problem that affects the quality of life of agricultural workers, this research objective to evaluate the postural load and musculoskeletal risk using the REBA Method to 40 workers growing and harvesting grafted cocoa on farms in the canton. Mocache, and the design of control measures. Using the GTC45 matrix for the identification of biomechanical risk, personal surveys and the Ergoniza software through the REBA Method as tools to evaluate vulnerable processes and postures. Fumigation presented a Risk and Intervention Level of II, meaning acceptable with control, being the activity with the highest Biomechanical Risk. The male sex predominated with 87.5%, 62.5% were under 45 years of age and had less than 10 working years, however, half reported musculoskeletal discomfort, and 89% of them were due to work, with the lumbar, dorsal and cervical spine being the identified segments; deficient medical surveillance but perception of the risk to which they are exposed. The inadequate postures with the highest risk evaluated, presented a High Risk Level (from 8 to 10) in the Cultivation process with scores of 10, 9 and 8, correcting the postures, it was reduced to Medium Risk (from 4 to 7) with scores of 4 and 5 except in Fumigation, with High Risk with a score of 8 due to the characteristics of the activity. In Harvest 3 of the activities presented medium risk (from 4 to 7) scoring 5 and 7, only two of its activities in Low Risk (from 2 to 3) with scores of 2. Proposing control measures to minimize the Risk Level of musculoskeletal injuries by process and activity, training workers, control of the postures adopted and Surveillance in Occupational Health. Keywords: Ergonomic evaluation, Inadequate postures, Musculoskeletal disorders